Evaluating Returns to Agricultural Research: A Review - Norton, George W.; Davis, J. S. (Wiley, 1981)
This paper reviews and compares the most common approaches used to evaluate public agricultural research investment. Ex post studies fall into two major groups: (a) consumer and producer surplus analyses, estimating average rates of return to research, and (b) production function analyses, estimating marginal rates of return to research. Ex ante studies fall into four groups: (a) those using scoring models to rank research activities, (b) those employing benefit‐cost analysis to establish rates of return to research, (c) those using simulation models, and (d) those using mathematical programming to select an optimal mix of research activities.